PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 003 SUNGAI MANASIB KECAMATAN BANGKO PUSAKO - Jopi gunawan Jopi gunawan; Damanhuri Daud Damanhuri Daud; Syahrilfud ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is a form of Classroom action research (CAR) consisting of two cycles using data collection techniques such as observation sheets and daily test students. Basic problem in this study is the low learning outcomes of students who indicated there are many students who are under the KKM. The purpose of this research is to improve science learning outcomes fifth grade students of SDN 003 Manasib River with the application of cooperative learning model Teams Games Tournament (TGT). This research was conducted at 003 River Elementary School fifth grade Manasib the number of students 28 people consisting of 13 men adan 15 people perempuan.Waktu study was conducted in April. The meter is measured student learning outcomes, mastery learning students, student activity. The results showed an increase in the activity of student learning outcomes at 1 cycle of 60% the first meeting. Then increased at the second meeting to 80%, an increase of 20%, the first meeting of the second cycle students 85% activity rate. Then increased at the second meeting to be 90%. And increase by 10%. I cycle daily test meetings unity average value 82.32% and the average cycle 2, 88.21%, completeness individual student learning in daily test 1 is 26 people with classical completeness 96.42%, and the daily test II 28 100 people with a classical completeness %, it can be concluded the increase in students' science learning outcomes. Keyword : Cooperative Learning Model type Teams Games Tournament (TGT), Science Learning Outcomes